The intersection between climate change, food, and migration: Transforming agri-food systems for human and planetary health - Fan, Shenggen (2019)
Today, the global food system finds itself facing major challenges. Mainly, they relate to changing diets, climate change, persistent conflicts and crises, and anti-globalisation sentiments, with implications at national, regional, and global levels. Rapid urbanisation and middle-class growth – resulting in changing diets – have been increasing pressure on food systems. At the same time, the growing impacts of climate change also threaten the agriculture industry, affecting productivity, prices, and food security. The percentage of Asian countries experiencing multiple climate shocks more than doubled to 51 per cent in 2011–2016, compared to 23 per cent in 1996–2000. In this context, multiple burdens of malnutrition also persist. In Asia, more than 83 million children under the age of five experience stunted growth, while over 17 million are overweight. In the Pacific, the percentage of overweight children under five rose to around nine per cent in 2017 from around five per cent in 2000. The percentage of overweight and obese adults are rising at a greater rate in Asia, with that of overweight females reaching 30 per cent in 2016 and 29 per cent amongst males. Further, these challenges are also interrelated, creating complex challenges for food security and nutrition – often disproportionately so for vulnerable groups.